A Critical Evaluation of the SKS Microfinance Fiasco - Pole, Prasad; Asawa, Anurag; Shah, Deepak (Indian Journal of Finance, 2014)
Crises have hit various players from different parts of the world in the global microfinance industry in the past. In the present study, we critically evaluate the SKS and Andhra Pradesh microfinance crisis in India. SKS established itself as a leader in the microfinance industry in India, and became the first listed microfinance company in the country. The dream run did not continue for long, as the Andhra Pradesh government started putting some regulatory conditions in place. We critically evaluate the SKS crisis to ascertain whether the cause was purely the government's action or the over-indebtedness amongst the borrowers of the microfinance industry. Further questions on commercialization of the microfinance industry are also discussed.